Perceived Effect of Merger on Employee Satisfaction on Nepalese Commercial Banks - Adhikari, Pitri Raj (Economic Review of Nepal, 2019)
The objective of this paper is to examine the perceived effect of merger on employee satisfaction of Nepalese commercial banks. Descriptive and casual comparative research design are used to estimate the relationship of employee satisfaction (dependent variable) with independent variables (pay remuneration, belonging, chain of command, training and development, employee performance, job security). Data are collected from 350 respondents of Kathmandu valley through structured questionnaires and descriptive and inferential statistics are used to analyse the data. The beta coefficients of pay remuneration, belonging, chain of command, training and development, employee performance and job security are positive and significant. According to respondents, increased size of the banks is the most important fact and improve employees’ satisfaction is the least important fact to merge of Nepalese banks. Similarly, most of the respondents’ states “change management of banks” is the major challenge of merged banks and “increased profitability of bank” is the least important challenge. It is observed that employees of banks ranked highest for belonging as the most important factor affecting their satisfaction of merged banks and it is also found that conceptualization of effect of merger and acquisition in Nepal is in the progressive stage and few institutions have been merged and are taking initiations on the broad aspects of employee satisfaction during merger as practices in developed countries.